Targeting mitochondrial quality control for treating sarcopenia: lessons from physical exercise. (1st February 2019) - Picca, Anna; Calvani, Riccardo; Leeuwenburgh, Christiaan; Coelho-Junior, Hélio José; Bernabei, Roberto; Landi, Francesco; Marzetti, Emanuele
ABSTRACT: Introduction : Mitochondrial dysfunction is a hallmark of aging and hence is a candidate target for intervention. Sarcopenia of aging is a prevalent condition and is associated with numerous negative health outcomes. Alterations in mitochondrial homeostasis have been reported in sarcopenic muscle. Area covered : We discuss the evidence that points to mitochondrial dysfunction having a causative role in sarcopenia and the mechanisms involved in the accumulation of damaged mitochondria in the aged muscle. We also discuss the effects of physical exercise on mitochondrial quality control and muscle health in advanced age. Expert opinion : In the aged muscle, the mitochondrial quality control axis is altered at several levels, including proteostasis, biogenesis, dynamics, and autophagy. Mitochondrial dysfunction arising from impaired quality control is thought to play a major role in the pathogenesis of sarcopenia. Physical exercise is the most effective strategy for the management of sarcopenia. Improvements in mitochondrial health and plasticity may mediate several beneficial effects of exercise in muscle. A greater understanding of the molecular changes that occur in the aged muscle following exercise and how they impact mitochondrial homeostasis is necessary for the exploration of potential targets that are amenable for interventions.